2016
DOI: 10.1002/jca.21507
|View full text |Cite
|
Sign up to set email alerts
|

Association of type II secretory phospholipase A2 and surfactant protein D with the pulmonary oxygenation potential in patients with septic shock during polymyxin‐B immobilized fiber‐direct hemoperfusion

Abstract: This study was undertaken to analyze the association of type II secretory phospholipase A 2 (sPLA 2 -II) and surfactant protein D (SP-D) with the pulmonary oxygenation potential in patients with septic shock during polymyxin-B immobilized fiber-direct hemoperfusion (PMX-DHP). The study was conducted in 25 patients with acute lung injury (ALI) or acute respiratory distress syndrome (ARDS). PMX-DHP lowered the blood endotoxin level in all patients. Following PMX-DHP, there were decreases from day 0 ! day 1 ! day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(36 reference statements)
0
5
0
1
Order By: Relevance
“…i) Phospholipase A 2 releases phospholipids that are metabolized through the enzyme system of the cyclooxygenases and lipooxigenesis in prostaglandins and leukotrienes ( 39 ). These substances determine fever (especially prostaglandin PGE 1 with effect the hypothalamus), vasodilation with increased cellular permeability ( 40 ). ii) The Hageman factor determines the initiation of the coagulation cascade and the activation of the quinine system.…”
Section: The Septic Syndromementioning
confidence: 99%
“…i) Phospholipase A 2 releases phospholipids that are metabolized through the enzyme system of the cyclooxygenases and lipooxigenesis in prostaglandins and leukotrienes ( 39 ). These substances determine fever (especially prostaglandin PGE 1 with effect the hypothalamus), vasodilation with increased cellular permeability ( 40 ). ii) The Hageman factor determines the initiation of the coagulation cascade and the activation of the quinine system.…”
Section: The Septic Syndromementioning
confidence: 99%
“…The first session of PMX‐DHP was started within 6 h of diagnosing patients with septic shock, with the duration of individual PMX‐DHP sessions ranging from 2 to 6 h depending on the patient’s condition . Our systolic blood pressure target was 120 mm Hg after 2 h of PMX‐DHP.…”
Section: Methodsmentioning
confidence: 99%
“…Endotoxin was measured immediately after obtaining the platelet‐rich plasma sample . Plasma endotoxin level was measured through a high‐sensitivity method (endotoxin‐specific turbidimetric time assay) using a Toxinometer ET‐500 (Wako Pure Chemical Industries, Ltd., Osaka, Japan), with a cutoff level for diagnosing endotoxemia set at 1.1 pg./mL .…”
Section: Methodsmentioning
confidence: 99%
“…Ishibe et al found that the plasma levels of type II secretory phospholipase A2 (sPLA2-II) and surfactant protein-D (SP-D) in patients with septic ARDS are simultaneously elevated with inflammatory cytokine levels (e.g., TNF-α and IL-8) [ 32 ]. sPLA2-II, excreted into the alveoli by macrophages and mast cells, plays an important role in the development of respiratory dysfunction.…”
Section: Introductionmentioning
confidence: 99%